The overgrowth of Ag controlled by K2PtCl4 based on gold nanorods. Issue 3 (April 2021) - Zhang, Qi; Deng, Tian-Song; Wei, Ming-Zhang; Gu, Yi-Jie; Cheng, Zhiqun
Abstract: Gold nanorods (AuNRs) have shown excellent performance in various fields such as biocatalysis, optical imaging, chemistry and medicine. Although bimetallic nanostructures based on gold nanorods have been widely used, how to effectively control the growth of the second metal is still a big challenge. To solve this problem, we develop this method to control the symmetric overgrowth of Ag shell based on gold nanorods. Here, we use K2 PtCl4 to be a precursor to form the AuNRs-Pt. And then AuNRs-Pt were used as seeds to form symmetric AuNRs-Pt-Ag by the addition of the AgNO3 precursor. The resulting products possess core-shell nanostructures and stronger localized surface plasmon resonances (LSPRs). Our approach can be widely extended to two or three metals in different shapes, which can be used in optical and catalytic applications.